Gaya Komunikasi Tokoh Masyarakat dalam Mengatasi Kenakalan Remaja di Desa Sayur Matinggi Kabupaten Simalungun - Sibuea, Idris Afandi; Rubino, Rubino; Bahri, Andini Nur (Lembaga Yasin AlSys, 2023)
This study aims to determine the style of communication used by community leaders in Sayur Matinggi Village, Ujung Padang District, Simalungun Regency and also to determine the obstacles and responses given in the application of communication styles in overcoming juvenile delinquency. In addition to knowing whether the communication style is in accordance with Islamic religious principles or not. This research method uses qualitative research methods with a descriptive approach. The informants in this study were three community leaders and 2 teenagers to become data sources. Data collection techniques carried out in this study used interview techniques, observation, and documentation related to research. The results of the research conducted are that the communication styles used by community leaders have been effective in overcoming juvenile delinquency, it's just that there are several communication styles that are not used because they have risks in use because they are threatening and aggressive. Obstacles in the application of communication styles in overcoming juvenile delinquency come from the surrounding environment which is less supportive for having a good personality. The language used by community leaders is also an obstacle in implementation because it uses regional languages and also many teenagers ignore orders given or ignore advice given. However, the response given by adolescents was quite positive, this can be seen in the development of knowledge insight in adolescents, being able to control emotions, and having a good personality. the style of communication used by community leaders is also in accordance with the principles of the Islamic religion and there is no visible deviation.